Pandangan Tokoh Masyarakat Desa Sei Bamban Terhadap Hukum Penyandingan Calon Pengantin Saat Akad Nikah - Muhammad Haqqin Nazili Batu Bara; Abd Mukhsin (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This study examines the practice of pairing prospective brides and grooms before the wedding ceremony in Sei Bamban Village, Batang Serangan District, Langkat Regency, which is rich in symbolic, social, and local cultural meaning. The research was conducted using qualitative methods through field observations and in-depth interviews with community leaders. Data were analyzed descriptively and qualitatively using a normative legal approach to examine the relationship between tradition and Islamic legal principles. The results show that the practice of pairing remains intact, and the role of community leaders is very central as guardians of cultural values, educators in providing religious understanding, and mediators in harmonizing customs with Islamic teachings. These findings emphasize the importance of synergy between culture and religion as a foundation for the formation of a harmonious local identity amidst the currents of modernization and social change.